微分
d{e^[(2x+1)^(1/2)]}
= e^[(2x+1)^(1/2)]d[(2x+1)^(1/2)]
= e^[(2x+1)^(1/2)](2x+1)^(-1/2)dx
d{sin(x)e^x}
= sin(x)d(e^x) + e^xd[sin(x)]
= sin(x)e^xdx + e^xcos(x)dx
= [sin(x) + cos(x)]e^xdx
积分
令 u = (2x+1)^(1/2), du = (2x+1)^(-1/2)dx, dx = udu.
Se^[(2x+1)^(1/2)]
= Sue^udu
= ue^u - Se^udu
= ue^u - e^u + C
= (u-1)e^u + C
= [(2x+1)^(1/2) - 1]e^[(2x+1)^(1/2)] + C
记 I = Ssin(x)e^xdx
I = sin(x)e^x - Se^xcos(x)dx
= sin(x)e^x - e^xcos(x) - Se^xsin(x)dx
= [sin(x) - cos(x)]e^x - I,
I = 0.5[sin(x) - cos(x)]e^x + C.
C = const.
1.∫e^√2x+1 dx=∫e^t d(t^2/2-1/2) 设√2x+1=t
=∫te^t dt
=te^t-∫e^t dt 分部积分
=te^t-e^t+c c是常数
=√2x+1e^√2x+1-e^√2x+1+c
2.∫sinx*e^x dx=(-cosx*e^x)+∫cosx*e^x dx 分部积分
∫cosx*e^x dx=sinx*e^x-∫sinx*e^x dx 分部积分
两式相减:解出∫sinx*e^x dx=1/2(-cosx+sinx)e^x+c c是常数
见图
1.∫e^√2x+1 dx=∫e^t d(t^2/2-1/2) 设√2x+1=t
=∫te^t dt
=te^t-∫e^t dt
=te^t-e^t+c
=√2x+1e^√2x+1-e^√2x+1+c
2.∫sinx*e^x dx=(-cosx*e^x)+∫cosx*e^x dx
∫cosx*e^x dx=sinx*e^x-∫sinx*e^x dx
解出∫sinx*e^x dx=1/2(-cosx+sinx)e^x+c
简单
微分1. d(e^√2x+1)=e^√2x+1d(√2x+1)=(e^√2x+1)/(√2x+1)dx
2. d(sinx·e^x)=sinxd(e^x)+e^xd(sinx)=e^x(sinx+cosx)dx
积分1.设(√2x+1)=t,则积分可转化:∫e^td(t^2/2-1/2)=∫te^tdt
运用分部积分法设:dv=e^tdt u=t
∫te^tdt=te^t-∫e^t dt =te^t-e^t+C
反换元得=√2x+1e^√2x+1-e^√2x+1+C
2.运用分部积分法设:u=sinx dv=e^xdx ∫sinxe^xdx=sinxe^x-∫e^xdsinx
=sinxe^x-∫e^xcosxdx
同理运用分部积分法∫e^xcosxdx=e^xcosx-∫sinxe^xdx
代入上式得∫sinxe^xdx=0.5e^x(sinx-cosx)+C